Integrating Behavioral Health Services in a Student-Run Medical Clinic - Belus, Jennifer M; Cohen, Matthew J; Givens, Matthew; Simirnova, Natalia; Myerholtz, Linda (Journal of Student-Run Clinics, 2017)
Integrating behavioral health services into a student-run medical clinic serves multiple purposes. One primary goal of such an initiative is to address the mental health needs of uninsured individuals who are more at risk for mental illness and less likely to seek help than individuals with insurance. An additional objective is to create a venue to train future healthcare providers in integrated healthcare models. This article describes the process of developing and implementing a behavioral health service within a well-established student-run medical clinic. Within the article, issues related to workflow, types of behavioral health services offered, patient recruitment, and clinical supervision are described. The purpose of this article is to explore key lessons learned and to inform other individuals and institutions interested in similarly integrating behavioral health services into current student-run health clinic models.